Perubahan Format dan Desain Surat Kabar Indonesia dalam Perspektif “McJournalism” - Ruswandi, Awang (Mediator, 2006)
The changing of newspapers format and design in Indonesia become a prominence phenomenon in recent times. When Kompas, a national leading newspaper in Indonesia, changed its format and design, it was sufficiently enough to claim that McJournalism phenomenon started to appear in Indonesia. McJournalism, adopted by Bob Franklin from Ritzer’s famous term “McDonaldization,” consisted of four characteristic: efficiency, calculability, predictability, and control. An analysis to such changes on some Indonesian major newspaper formats and designs have proven that the policy led also to the changing of mechanisms and working routines in those newspapers as well.